Efektivitas Penggunaan Media Quizizz pada Mata Pelajaran Sejarah Kelas X SMK - Rahayu, Anny; Adam, Andi; Nasir (Almeera Education, 2022)
Research on the Effectiveness of Using Quizizz Media in History Subjects of diachronic, synchronic, chronological, space and time concepts in history. Class X DKV (Virtual Communication Design) students at SMK Negeri 1 Karossa for the 2022/2023 academic year, with a total of 16 students. Aims to determine the effectiveness of using quizizz media in history subjects. The sample in this study were students of class X DKV (Virtual Communication Design), the method used in this study was an experimental method with a quantitative approach. The instruments in this study used tests, questionnaires, and documentation. Data collection techniques used are tests, questionnaires and documentation. data analysis technique by Descriptive Statistics analysis and Inferential Statistics analysis. The results of the descriptive statistical analysis showed that the average student learning outcomes before using the quizizz media was 47.25, the student's score was still below the KKM score and after using the quizizz media, the average student score was 89.81, an increase above the KKM score. For inferential statistical analysis using the t test formula, it is known that a significant value of 0.000 <0.05 is obtained so that H0 is rejected and H1 is accepted. Based on these results, it shows that the use of quizizz media is effective in history subjects for class X DKV (Virtual Communication Design) SMK Negeri 1 Karossa, Central Mamuju Regency.